Poetry's Law - Joe Luna (Journal of British and Irish Innovative Poetry, 2019)
This essay tries to interpret Anna Mendelssohn’s poetry by thinking about the ways in which her poetry consistently returns to the matter of her survival. It closely reads Mendelssohn's correspondence with Douglas Oliver and her poetry of the late 1990s, first by identifying the role played by the enemies of poetry in that writing, and second by attempting to account for this role in terms of both Anna Mendelssohn's life as a poet, and the formal political responsibilities and necessities by which the poetry is animated. The essay locates a formal precedent that illuminates both of these roles in traditional Jewish lamentation, and Mendelssohn's work is identified with this tradition in order to unpack the complexity of her embattled lyric oeuvre. The essay further suggests that Mendelssohn's insistent anti-political stance throughout her writing life entails a politics of communitarian solidarity to be found only within the remit of poetic writing. The name for this radically negative aesthetic foundation is the title of the essay.